Endothelial Function in Stroke Subtypes Using Endopat Technology - Enrique Jiménez Caballero, Pedro; López Espuela, Fidel; Carlos Portilla Cuenca, Juan; Antonio Fermin Marrero, José; Casado Naranjo, Ignacio (Journal of Neurological Research And Therapy, 2015)
Background. Endothelial function is characterized by the vasodilator capacity of blood vessel smooth muscle cells mediated by nitric oxide. Some studies have shown an inverse association between the endothelial function and the carotid intima-media thickness (IMT). The relationship between endothelial dysfunction and stroke based on several studies has shown that is altered in all stroke subtypes especially lacunar strokes. Methods. We aimed to investigate endothelial function by EndoPAT device in relation to stroke subtypes. We investigate too the correlations between endothelial function and IMT and we study possible interactions with age, sex, traditional risk factors and severity of stroke. Subsequent patients with acute ischemic stroke were enrolled. They were divided according with the etiological mechanism of stroke (TOAST classification). Endothelial function was assessed with finger plethysmography by the EndoPAT device that gave Reactive Hyperemia Index (RHI) and Augmentation Index (AI). Results. Patients with a cardioembolic stroke had a RHI higher than atherotrombotic or lacunar stroke. There was a negative correlation between RHI and IMT and positive between AI and age. Conclusions. The endothelial function is different between stroke subtypes with higher values of RHI in the cardioembolic respect to lacunar or atherotrombotic. The RHI is correlated with the atherosclerosis by the negative relationship with the IMT. The AI that shows the rigidity in the arteries increased with the age.
Keywords: Endothelial Dysfunction; Ischemic Stroke; Stroke Subtypes; Carotid Intima-Media Thickness; Reactive Hyperemia Index; Augmentation Index; EndoPAT